2014
DOI: 10.1371/journal.pgen.1004449
|View full text |Cite
|
Sign up to set email alerts
|

Souffle/Spastizin Controls Secretory Vesicle Maturation during Zebrafish Oogenesis

Abstract: During oogenesis, the egg prepares for fertilization and early embryogenesis. As a consequence, vesicle transport is very active during vitellogenesis, and oocytes are an outstanding system to study regulators of membrane trafficking. Here, we combine zebrafish genetics and the oocyte model to identify the molecular lesion underlying the zebrafish souffle (suf) mutation. We demonstrate that suf encodes the homolog of the Hereditary Spastic Paraplegia (HSP) gene SPASTIZIN (SPG15). We show that in zebrafish oocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 109 publications
3
43
0
Order By: Relevance
“…Although spatacsin and spastizin have been shown to associate with AP-5 ( 3 , 4 ), there are conflicting reports about the function of spastizin ( 3 , 22 24 ), as well as the obligate nature of their association ( 5 , 25 ). Here we qualify their relationship and show that depletion of spastizin using siRNA in HeLa cells leads to reduction of the protein levels of both AP-5 ζ and µ5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although spatacsin and spastizin have been shown to associate with AP-5 ( 3 , 4 ), there are conflicting reports about the function of spastizin ( 3 , 22 24 ), as well as the obligate nature of their association ( 5 , 25 ). Here we qualify their relationship and show that depletion of spastizin using siRNA in HeLa cells leads to reduction of the protein levels of both AP-5 ζ and µ5 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these observations suggest that AP-5 is dependent on spatacsin and spastizin for either its assembly or its recruitment to membranes, but the converse is not true as spatacsin and spastizin are still recruited to membrane in the absence of AP-5 (see also 4 , 25 ). The fact that spatacsin and spastizin may be able to function in the absence of AP-5 may help explain alternative functions attributed to SPG15, such as in dense core granule formation ( 22 ), or its role in autophagosome fusion ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…As CGs exocytose, membrane must be retrieved, presumably through a process such as Clathrin-mediated endocytosis (Bement et al, 2000;Tsai et al, 2011), and indeed both Clathrin and Dynamin have been found to localize to at least a subset of CGs (Faire and Bonder, 1993;Kanagaraj et al, 2014). After exocytosis, F-actin undergoes rapid reassembly to enclose the edges of endocytosing crypts at sites of previous exocytotic events (Becker and Hart, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Functional studies in zebrafish showed that knockdown of the zebrafish SPG15 ortholog (suf ) led to motor axon outgrowth failure and motor impairment (Martin et al, 2012). However, Kanagaraj et al (2014) found that zygotic zebrafish suf −/− embryos did not show a neurological phenotype or motor axon outgrowth failure, while they confirmed, after the MO injection, the previously reported severe phenotypes (Kanagaraj et al, 2014). These authors described an uncharacterized cellular mechanism for suf/spastizin activity during secretory vesicle maturation in zebrafish oogenesis, which raised the possibility of novel avenues for HSP therapy research (Kanagaraj et al, 2014).…”
Section: Spg15mentioning
confidence: 99%